The role of human resources management in promoting international business - Khetiri, Wahiba; Bouallags, Noura; Boulhout, Abdelmadjid (Finance and Business Economies Review, 2020)
The study aims to identify the role that human resources management plays in improving business performance at the international level, by identifying the nature of the relationship that links the administrative side to international business. In order to reach this goal, an analytical study has been drawn on the human resource that is active outside the borders of The state, the nature of the activity of the institutions attracted to it and its aspirations to preserve it was concluded that the necessity of providing a suitable climate for the human resource in order to move its motivations and encourage it to work outside the borders of its state, with an interest in its training and formation on an ongoing basis because it constitutes the strength of the institution and one of its sources of advantage Witch.